Deep radiostratigraphy of the East Antarctic plateau: connecting the Dome C and Vostok ice core sites - Cavitte, Marie, M; Blankenship, Donald, D; Young, Duncan, A; Schroeder, Dustin, J; Parrenin, Frédéric; Lemeur, Emmanuel; Macgregor, Joseph, J; Siegert, Martin, J (Journal of Glaciology, 2016)
International audience Several airborne radar-sounding surveys are used to trace internal reflections around the European Project for Ice Coring in Antarctica Dome C and Vostok ice core sites. Thirteen reflections, spanning the last two glacial cycles, are traced within 200 km of Dome C, a promising region for million-year-old ice, using the University of Texas Institute for Geophysics High-Capacity Radar Sounder. This provides a dated stratigraphy to 2318 m depth at Dome C. Reflection age uncertainties are calculated from the radar range precision and signal-to-noise ratio of the internal reflections. The radar stratigraphy matches well with the Multichannel Coherent Radar Depth Sounder (MCoRDS) radar stratigraphy obtained independently. We show that radar sounding enables the extension of ice core ages through the ice sheet with an additional radar-related age uncertainty of ∼1/3–1/2 that of the ice cores. Reflections are extended along the Byrd-Totten Glacier divide, using University of Texas/Technical University of Denmark and MCoRDS surveys. However, core-to-core connection is impeded by pervasive aeolian terranes, and Lake Vostok's influence on reflection geometry. Poor radar connection of the two ice cores is attributed to these effects and suboptimal survey design in affected areas. We demonstrate that, while ice sheet internal radar reflections are generally isochronal and can be mapped over large distances, careful survey planning is necessary to extend ice core chronologies to distant regions of the East Antarctic ice sheet.